Service and Protocol Architecture for the MAFTIA Middleware - Cachin, C. (2009)
This document describes the specification of the MAFTIA middleware architecture. This specification focusses on the models, building blocks and services. It describes the tradeoffs made in terms of models, the choices of building blocks and their topology, and the portfolio of services to be offered by the MAFTIA middleware to applications and high-level services. In particular, regarding the system model, it presents a detailed discussion on the fault, synchrony, topological, and group models, which were used to guide the overall architecture. The architecture was divided into two main levels, the site part which connects to the network and handles all inter-host operations, and a participant part which takes care of all distributed activities and relies on the services provided by the site-part components